Patient Intimacy and Innovation Development to Improve Health Service Performance - Tri Ratnasari, Ririn; Gunawan, Sri; Qudzi Fauzi, Moh; Fitrisia Septiarini, Dina (International Journal of Engineering and Technology, 2018)
This study aim to determine the impact of patient intimacy and developing innovations to improve the performance of health services in public health centers which ISO certified in Surabaya. This research was conducted with a quantitative approach survey to patients who are on treatment or health check at public health center. The sampling technique is simple random sampling. Furthermore, the data were processed using partial least square. Result from this study are first, communicaton, social interaction, and compromise as part of a patient intimacy significantly affect the performance of health service in health centers which certified by ISO. Second, communication, compromise, and social interaction as part of the patient intimacy have significant impact on the innovation development of public health centers which certified by ISO. Third, the innovations development significantly affect the performance of health services in primary public health centers which have ISO certificate.Â Â